Pediatric Readiness in Emergency Medical Services Systems. (3rd March 2020) - Moore, Brian; Shah, Manish I.; Owusu-Ansah, Sylvia; Gross, Toni; Brown, Kathleen; Gausche-Hill, Marianne; Remick, Katherine; Adelgais, Kathleen; Lyng, John; Rappaport, Lara; Snow, Sally; Wright-Johnson, Cynthia; et al.
Abstract: This is a joint policy statement from the American Academy of Pediatrics, American College of Emergency Physicians, Emergency Nurses Association, National Association of Emergency Medical Services Physicians, and National Association of Emergency Medical Technicians on pediatric readiness in emergency medical services systems.